Th17 Cells in Autoimmune and Infectious Diseases - José Francisco Zambrano-Zaragoza; Enrique Jhonatan Romo-Martínez; Ma. de Jesús Durán-Avelar; Noemí García-Magallanes; Norberto Vibanco-Pérez (Hindawi Limited, 2014)
The view of CD4 T-cell-mediated immunity as a balance between distinct lineages of Th1 and Th2 cells has changed dramatically. Identification of the IL-17 family of cytokines and of the fact that IL-23 mediates the expansion of IL-17-producing T cells uncovered a new subset of Th cells designated Th17 cells, which have emerged as a third independent T-cell subset that may play an essential role in protection against certain extracellular pathogens. Moreover, Th17 cells have been extensively analyzed because of their strong association with inflammatory disorders and autoimmune diseases. Also, they appear to be critical for controlling these disorders. Similar to Th1 and Th2 cells, Th17 cells require specific cytokines and transcription factors for their differentiation. Th17 cells have been characterized as one of the major pathogenic Th cell populations underlying the development of many autoimmune diseases, and they are enhanced and stabilized by IL-23. The characteristics of Th17 cells, cytokines, and their sources, as well as their role in infectious and autoimmune diseases, are discussed in this review.